2022
DOI: 10.3390/vetsci9090507
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Zinc Deficiency Aggravated Intestinal Barrier Dysfunction and Inflammation through ETEC Virulence Factors in a Mouse Model of Diarrhea

Abstract: Zinc is both essential and inhibitory for the pathogenesis of enterotoxigenic Escherichia coli (ETEC). However, the accurate effects and underlying mechanism of marginal zinc deficiency on ETEC infection are not fully understood. Here, a marginal zinc-deficient mouse model was established by feeding mice with a marginal zinc-deficient diet, and ETEC k88 was further administrated to mice after antibiotic disruption of the normal microbiota. Marginal zinc deficiency aggravated growth impairment, diarrhea, intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…At the same time, the pathogenicity of ETEC is based on the secretion of LT and ST in the intestinal epithelium, which are the main causes of diarrhea symptoms [ 3 ]. Previous studies have demonstrated that dZn can obviously upregulate the mRNA expression of virulence genes in the cecum contents of ETEC infection mice [ 14 ]. In the present study, the increased expression of genes involved in cellular adhesion (FaeG), LT (eltA and eltB), ST (estB), and biofilm formation (bssS) in the cecum of mice induced by ETEC infection was prevented by pretreatment with ZnLa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, the pathogenicity of ETEC is based on the secretion of LT and ST in the intestinal epithelium, which are the main causes of diarrhea symptoms [ 3 ]. Previous studies have demonstrated that dZn can obviously upregulate the mRNA expression of virulence genes in the cecum contents of ETEC infection mice [ 14 ]. In the present study, the increased expression of genes involved in cellular adhesion (FaeG), LT (eltA and eltB), ST (estB), and biofilm formation (bssS) in the cecum of mice induced by ETEC infection was prevented by pretreatment with ZnLa.…”
Section: Discussionmentioning
confidence: 99%
“…The ETEC infection was performed in accordance with our previous study [ 14 ]. Briefly, mice were treated with streptomycin (5 g/L) and fructose (67 g/L) in drinking water 36 h before the ETEC infection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation